The Holy Spirit : the key to supernatural living - Bright, Bill, 1921-2003 (Campus Crusade for Christ International : Here's Life Publishers, 1980)
This book is designed to help the reader discover the joy of being a Christian. Includes information and guides on applying and using the power of the Holy Spirit in our everyday lives.